Dismenorea pada Mahasiswa Fakultas Kedokteran dalam Kaitannya dengan Pengetahuan dan Stres - Asmalia, Resy; Anggina, Dientyah Nur; Badri, Putri Rizki Amalia; Ghifari, Muhammad Zulisandi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
Dysmenorrhea is pain that occurs during menstruation, which is mostly suffered by young women. Dysmenorrhea is caused by many factors, including knowledge and stress. Medical students have higher stress due to academic demands that exceed students' abilities, which tends to affect dysmenorrhea. This study aimed to determine the relationship between knowledge and stress with dysmenorrhea pain in students of the Faculty of Medicine, Muhammadiyah University of Palembang. The design of this study was cross-sectional, involving 86 female students of the Faculty of Medicine, Muhammadiyah University of Palembang, who were selected using the total sampling technique. Data were collected by filling out questionnaires, namely a questionnaire on knowledge about dysmenorrhea, a questionnaire on the level of dysmenorrhea and a DASS questionnaire for stress levels. Data analysis was performed using the Chi-square test. The results showed that the most knowledge was good (98.8%), the most stress level was severe (67.4%) and the most pain was severe dysmenorrhea (53.5%). The p-value for knowledge was 0.465 (not correlated with dysmenorrhea pain) and for stress was 0.170 (not correlated with dysmenorrhea pain). Furthermore, it was concluded that dysmenorrhea pain in female students of the Faculty of Medicine, Muhammadiyah University of Palembang was not related to knowledge and stress.Keywords: dysmenorrhea; medical students; knowledge; stress ABSTRAK Dismenorea merupakan nyeri yang terjadi saat menstruasi, yang mayoritas diderita oleh wanita muda. Dismenorea disebabkan banyak faktor, di antaranya adalah pengetahuan dan stress. Mahasiswa kedokteran memiliki stres lebih tinggi karena tuntutan akademik yang melebihi kemampuan mahasiswa, sehingga cenderung mempengaruhi dismenorea. Penelitian ini bertujuan untuk mengetahui hubungan antara pengetahuan dan stres dengan nyeri dismenorea pada mahasiswa Fakultas Kedokteran, Universitas Muhammadiyah Palembang. Desain penelitian ini adalah cross-sectional, yang melibatkan 86 mahasiswa putri Fakultas Kedokteran, Universitas Muhammadiyah Palembang, yang diseleksi menggunakan teknik total sampling. Data dikumpulkan melalui pengisian kuesioner yaitu kuesioner pengetahuan mengenai dismenorea, kuesioner tingkat dismenorea dan kuesioner DASS untuk tingkat stres. Analisis data dilakukan menggunakan uji Chi-square. Hasil penelitian menunjukkan bahwa pengetahuan terbanyak adalah baik (98,8%), tingkat stres terbanyak adalah berat (67,4%) dan nyeri terbanyak adalah dismenorea berat (53,5%). Nilai p untuk pengetahuan adalah 0,465 (tidak berkorelasi dengan nyeri dismenorea) dan untuk stres adalah 0,170 (tidak berkorelasi dengan nyeri dismenorea). Selanjutnya disimpulkan bahwa nyeri dismenorea pada mahasiswa putri Fakultas Kedokteran, Universitas Muhammadiyah Palembang tidak berhubungan dengan pengetahuan dan stres.Kata kunci: dismenorea; mahasiswa kedokteran; pengetahuan; stres